Shaping customer engagement, repurchase intention and positive word-of-month in omnichannel retailing context - Lopes, Ana Catarina Horta (2020)
A seamless experience across different channels is a present challenge for all brands. Omnichannel is shaping customers' needs and expectations, brands must evolve their efforts to engage and empower their customers across several channels. The aim of this dissertation is to provide insights on how customer engagement and its outcomes, repurchase intention and positive word-of-mouth, change in an omnichannel environment. Thus, a research model was drawn and tested based on social exchange theory to explain customer engagement in an omnichannel environment. Two studies were conducted to better understand the proposed model: the first study with a secondary data approach provided insights on the market the study was conducted in: the skin care market in Portugal. Study number two used primary data to test the proposed model and its hypotheses through partial least square analysis. The findings of the study show that customer channel familiarity and channel integration quality are, indeed, related to customer engagement and its outcomes. However, customer empowerment was not found significant as a mediating effect between customer channel familiarity and customer engagement. This is mainly related to offline channels not being fully owned by skin care brands, which difficult their empowering effect towards customers. Nevertheless, customer empowerment is a mediating effect of channel integration quality and customer engagement. A consistent integration of channels makes customers feel more empowered, and, consequently, more engaged leading customers to repurchase brands’ products and sharing positive comments about the brand with others.